2020
DOI: 10.1116/6.0000641
|View full text |Cite
|
Sign up to set email alerts
|

Modified atomic layer deposition of MoS2 thin films

Abstract: As one of the most attractive transition metal dichalcogenides (TMDs), the growth of molybdenum disulfide (MoS2) with industrial compatibility is of great importance. Atomic layer deposition (ALD) has been shown to be a promising method to achieve the growth of high-quality TMD materials. However, MoS2 films deposited by ALD often are amorphous with nonideal stoichiometry and require high-temperature post-deposition annealing. In this study, we introduce a modified ALD recipe using Mo(CO)6 and H2S, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Another study by Liao and Ekerdt of both Ru 3 (CO) 12 and ruthenium bis(di-t-butylacetamidinate) dicarbonyl [Ru( t Bu-Me-amd) 2 (CO) 2 ] precursors observed that growth rate increased with temperature, without evidence of CO decomposition into other inert species such as graphitic carbon, again in line with our proposed mechanism involving simple CO desorption. [83] Further evidence for this mechanism of growth dependence on CO release is found in a recent ALD report of Mo(CO) 6 used to synthesize MoS 2 with H 2 S. [39] While that system contains a different metal center and reacts on a different growth surface, Mo(CO) 6 is a zero-oxidation state precursor containing CO ligands, similar to Ru(DMBD)(CO) 3 . Zeng et al found that at lower temperatures and purge times, the CO ligands were not completely removed and were instead incorporated into the film as impurities.…”
Section: Growth Mechanismmentioning
confidence: 90%
See 4 more Smart Citations
“…Another study by Liao and Ekerdt of both Ru 3 (CO) 12 and ruthenium bis(di-t-butylacetamidinate) dicarbonyl [Ru( t Bu-Me-amd) 2 (CO) 2 ] precursors observed that growth rate increased with temperature, without evidence of CO decomposition into other inert species such as graphitic carbon, again in line with our proposed mechanism involving simple CO desorption. [83] Further evidence for this mechanism of growth dependence on CO release is found in a recent ALD report of Mo(CO) 6 used to synthesize MoS 2 with H 2 S. [39] While that system contains a different metal center and reacts on a different growth surface, Mo(CO) 6 is a zero-oxidation state precursor containing CO ligands, similar to Ru(DMBD)(CO) 3 . Zeng et al found that at lower temperatures and purge times, the CO ligands were not completely removed and were instead incorporated into the film as impurities.…”
Section: Growth Mechanismmentioning
confidence: 90%
“…[82] Further evidence for this mechanism of growth dependence on CO release is found in a recent ALD report of Mo(CO)6 use to synthesize MoS2 with H2S. [39] While that system contains a different metal center and reacts on a different growth surface, Mo(CO)6 is a zero-oxidation state precursor containing CO ligands, similar to Ru(DMBD)(CO)3. Zeng et al found that at lower temperatures and purge times, the CO ligands were not completely removed and were instead incorporated into the film as impurities.…”
Section: Growth Mechanismmentioning
confidence: 90%
See 3 more Smart Citations